Humanitarian intervention : a history - Simms, Brendan; Trim, D. J. B. (Cambridge ; New York : Cambridge University Press, 2011)
"The dilemma of how best to protect human rights is one of the most persistent problems facing the international community today. This unique and wide-ranging history of humanitarian intervention examines responses to oppression, persecution and mass atrocities from the emergence of the international state system and international law in the late sixteenth century, to the end of the twentieth century. Leading scholars show how opposition to tyranny and to religious persecution evolved from notions of the common interests of 'Christendom' to ultimately incorporate all people under the concept of 'human rights'. As well as examining specific episodes of intervention, the authors consider how these have been perceived and justified over time, and offer important new insights into ideas of national sovereignty, international relations and law, as well as political thought and the development of current theories of 'international community'"--
Machine generated contents note: 1. Towards a history of humanitarian intervention Brendan Simms and D. J. B. Trim; Part I. Early-Modern Precedents: 2. 'If a prince use tyrannie towards his people': interventions on behalf of foreign populations in early-modern Europe D. J. B. Trim; 3. The Protestant interest and the history of humanitarian intervention, c.1685-c.1756 Andrew Thompson; 4. 'The age of chivalry is not dead': the idea of humanitarian intervention in the era of Burke Brendan Simms; Part II. The Great Powers and the Ottoman Empire: 5. 'From an umpire to a competitor': Castlereagh, Canning and the issue of international intervention in the wake of the Napoleonic Wars John Bew; 6. Intervening in the Jewish question, 1840-1878 Abigail Green; 7. The 'principles of humanity' and the European powers' intervention in Ottoman Lebanon and Syria in 1860-61 Davide Rodogno; 8. The guarantees of humanity: the Concert of Europe and the origins of the Russo-Ottoman War of 1877 Matthias Schulz; 9. The European powers' intervention in Macedonia, 1903-1908: an instance of humanitarian intervention? Davide Rodogno; Part III. Intervening in Africa: 10. The price of legitimacy in humanitarian intervention: Britain, the European powers and the abolition of the West African slave trade, 1807-1867 Maeve Ryan; 11. British anti-slave trade and anti-slavery policy in East Africa, Arabia, and Turkey in the late nineteenth century William Mulligan; 12. The origins of humanitarian intervention in Sudan: Anglo-American missionaries after 1899 Gideon Mailer; Part IV. Non-European States: 13. Humanitarian intervention, democracy, and imperialism: the American war with Spain, 1898, and after Mike Sewell; 14. The innovation of the Jackson-Vanik Amendment Thomas Probert; 15. Fraternal aid, self-defence, or self-interest? Vietnam's intervention in Cambodia (1978-1989) Sophie Quinn-Judge; Part V. Postscript: 16. Humanitarian intervention since 1990 and 'liberal interventionism' Matthew Jamison; 17. Humanitarian intervention in historical perspective D. J. B. Trim.
Keywords: Humanitarian intervention; Humanitarian intervention -- Case studies